Climate change concerns and information spillovers from socially-connected friends - Maximilian Mayer (Halle Institute for Economic Research (IWH), 2023)
This paper studies the role of social connections in shaping individuals' concerns about climate change. I combine granular climate data, region-level social network data and survey responses for 24 European countries in order to document large information spillovers. Individuals become more concerned about climate change when their geographically distant friends living in sociallyconnected regions have experienced large increases in temperatures since 1990. Exploring the heterogeneity of the spillover effects, I uncover that the learning via social networks plays a central role. Further, results illustrate the important role of social values and economic preferences for understanding how information spillovers affect individual concerns.
Keywords: D01; D62; D64; D8; Q5; 330; beliefs; climate change; information spillovers; social networks